Female Elementary Teachers’ Biopedagogical Practices: How Health Discourse Circulates in Newfoundland Elementary Schools - Petherick, LeAnne; Beausoleil, Natalie (Canadian Journal of Education/Revue canadienne de l’éducation, 2015)
Epidemiological data construct the population of Newfoundland and Labrador as being one of the most obese populations in Canada. The concern for child and youth health is particularly pertinent within school culture and places teachers in precarious positions where they are being asked to share in shaping healthy lifestyle messages while also considering their own health practices. Based on interviews with 13 female elementary school teachers, we explore the ways in which dominant health messages are taken up but also challenged by teachers within school culture. A thematic analysis of teachers’ narratives highlights the moral values used in the promotion of eating and exercising in school staff rooms, the gendered and sometimes romanticized view of the past as a method for communicating contemporary health concerns, the struggle to challenge dominant health discourses, and finally, the tensions that arise for people when thinking more complexly about health and healthy living. Teachers’ concern for biopedagogical practice demonstrates how they continuously challenge but also participate in the production of the health imperative.